DISPENSASI PERKAWINAN DI BAWAH UMUR MENURUT ULAMA DAN UNDANG-UNDANG - Zulkifli zulkifli (IAIN Palopo, 2021)
This study aims to examine the views of scholars regarding the age limit for marriage and the laws and regulations that underlie the implementation of marriage dispensation. This type of research uses library research, collects primary and secondary data by means of documentation, and analyzes it using content analysis techniques. This study concludes that scholars do not provide a firm enough limit on the age limit for marriage and there is no agreement on this matter. Globally, the ulemas only require the existence of a maturity factor between the two parties. The age limit mentioned by the scholars is between fifteen and eighteen years. The minimum age limit of nineteen years aims to protect children's rights, and avoid things that hinder physical and mental development. Under certain conditions, a dispensation can be granted based on legal facts proven in court that the marriage is very urgent to take place in order to realize the goals of Islamic law.